2000 IEEE MTT-S International Microwave Symposium Digest (Cat. No.00CH37017)
DOI: 10.1109/mwsym.2000.860889
|View full text |Cite
|
Sign up to set email alerts
|

Accurate RF and microwave system level modeling of wideband nonlinear circuits

Abstract: International audienceAccurate system level simulation is indispensable for efficient RF communication system design. However system level models of nonlinear circuits are today very limited by their inability to handle nonlinear memory effects. The paper describes a new approach of system-level modeling which accounts efficiently for nonlinear envelope memory effects of wideband amplifiers, multipliers and mixers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Figure 5 shows the IMD at 2f 1 -f 2 and 2f 2 -f 1 for a fixed input power of -10 dBm as a function of the frequency spacing ∆f. The increment of the IMD as the tone spacing decreases and the aforementioned asymmetry between the IMD might be due to several origins, but in general they might be attributed to the existence of memory effects with time constants similar to the period of the modulating signal (frequency ∆f) in a two tone IMD experiment [11], [12].…”
Section: Imd Measurements In Fbarmentioning
confidence: 99%
“…Figure 5 shows the IMD at 2f 1 -f 2 and 2f 2 -f 1 for a fixed input power of -10 dBm as a function of the frequency spacing ∆f. The increment of the IMD as the tone spacing decreases and the aforementioned asymmetry between the IMD might be due to several origins, but in general they might be attributed to the existence of memory effects with time constants similar to the period of the modulating signal (frequency ∆f) in a two tone IMD experiment [11], [12].…”
Section: Imd Measurements In Fbarmentioning
confidence: 99%
“…From equation (4) and reporting to reference [4], it is easily shown that the S parameters terms in (5) are unambiguously determined by the setup sketched in reference [4], where the circuit bloc is driven by a two-tone signal ( ) with three different impedances as described in [12]. To fully characterize the circuit bloc, the amplitude 1 A of the incident wave is swept from small signal operation to saturation, and the frequency of the small tone Ω is swept thought the bloc operation bandwidth.…”
Section: Extraction Of the Nonlinear S Parametersmentioning
confidence: 99%
“…Since in practice, the amplifier or mixer bloc should work close to the impedance matching conditions, we will assume that the incident waveform ( ) 2 a t at the output, will be relatively small, so that the relation defined by equation (3) a t and the assumption of short memory duration of the circuit bloc as compared to the signal envelope speed (that is usually valid in narrow modulation bandwidth applications), we may limit the power expansion to first order, and straightforwardly derive the following expression of reflected waveforms. We may observe that (4) is an extension of the model expression reported in [4], that handles both input and output impedance mismatch, through the dependence to both input and output incident waves. The circuit bloc is thus characterized by the static Volterra kernels Ω Ω Equation (5) defines the notion of nonlinear S parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the number of coefficients to be estimated in the model increases exponentially with the degree of nonlinearity and with the memory length of the system. To overcome the modeling complexity, various model-order reduction approaches have been proposed to simplify the Volterra model structure [5][6][7][8][9][10][11][12][13][14][15]. Although these simplified models have been employed to characterize PAs with reasonable accuracy under certain conditions, there is no systematic way to verify if the model structure chosen is truly appropriate to the PA under study.…”
Section: Introductionmentioning
confidence: 99%